Cereal grains : properties, processing, and nutritional attributes / Sergio R Othón Serna Saldívar - Serna Saldívar, Sergio R. Othón
Focusing on postharvest management and the wide array of industrial processes used to manufacture foods, this book provides information about the physicochemical and nutritional properties of cereals and their products. It covers the chemical and physical grain properties of various types of cereals and cereal-based products.